Hegel on “Negotiating Transcendence” - Ormiston, Alice (Ethnologies, 2003)
AbstractThis article examines what Hegel’s political philosophy might have to offer to contemporary thinking on transcendence. Hegel’s thinking is seen to be significant because it explores the possibility of spiritual transcendence in the context of a modern consciousness that is secular in orientation, and relatively alienated from spiritual experience. Focusing on the experience of love in childhood, and the ongoing way in which love manifests itself in the life cycle of the modern individual, Hegel offers an idea of transcendence that is rooted in our everyday, secular existence, and expressed in our ethical and political engagement with others. It seeks to comprehend how we might overcome the rigid duality between finite and infinite, secular and religious, mundane and extraordinary, within our own existence.